Northern Pontic Antiquities in the State Hermitage Museum - Boardman, John,; Solovyov, Sergei,; Tsetskhladze, G.R., (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
This volume, written by staff of the State Hermitage, one of the world's finest museums, publishes Graeco-Roman antiquities kept there. Much of the material has been unearthed during the museum's field projects in Berezan, Myrmekion and Nymphaeum. Many items are published here for the first time. In addition, there are new studies and reinterpretations of well-known material. The book also contains reviews and notes on new publications on the Black Sea from Eastern and Western Europe and North America. The volume provides a good account of the manifold activities in which the staff of the Department of the History and Culture of the Ancient World, and of the Hermitage in general, are engaged. The book is very richly illustrated, with nearly 150 photographs, line drawings, maps etc.